The Implementation of Independent Reading Literacy Activities in Secondary Education - Cahya, Wahyu Dwi; Artini, Luh Putu; Padmadewi, Ni Nyoman (LPPM Undiksha, 2020)
The present study aimed at describing the implementation of independent reading literacy activities at SMA N Bali Mandara and how it affects students’ English literacy skills. This study followed case study design, and the primary data were obtained through interview, observation, and document analysis. The results of the study revealed that the implementation of independent reading literacy activities was applied in three stages: 1) the habituation stage; 2) the development stage; and 3) the learning stage. In the habituation stage, the school used silent reading to form reading habits. This positive habit maintained by providing students real-world literacy activities in the development stage to develop their reading interest through storybook writing and cooperative literacy program. In the last stage, the teachers implemented reading for enjoyment in the learning process through news reading and book review. The students’ average score in storybook writing was 90.6, in cooperative literacy program was 90.36, in news reading program was 90.2, and in book review was 90.47. The findings of this study indicate that independent reading literacy activities are effective to enhance students’ English literacy skills.